The effect of epithelial and stromal tumor components on FIGO stages III and IV ovarian carcinosarcomas treated with primary surgery and chemotherapy. Issue 5 (1st September 2007) - Athavale, R.; Thomakos, N.; Godfrey, K.; Kew, F.; Cross, P.; De Barros Lopes, A.; Hatem, M. H.; Naik, R.
Abstract : The aim of this study is to assess the effect of epithelial and stromal tumor components on survival outcomes in FIGO stage III or IV ovarian carcinosarcomas (OCS) treated with primary surgery and adjuvant chemotherapy at the Northern Gynaecological Oncology Centre (NGOC), Gateshead. Women were identified from the histopathology/NGOC databases. Age, FIGO stage, details of histology, treatment, and overall survival were recorded. Of 34 cases (1994–2006, all FIGO stages), 17 were treated with primary surgery followed by adjuvant chemotherapy for FIGO stage III or IV. The median age was 66 years (52–85 years). Cytoreduction was optimal ( n = 9) or complete ( n = 1) in 10/17 (59%) cases. Epithelial predominant (EP) or stromal predominant (SP) tumor (defined as >50% of either component in the primary tumor) was noted in 12 and 5 cases, respectively. Epithelial types included serous ( n = 9), endometrioid ( n = 5), and mixed types ( n = 3). Twelve women have died of disease. The median overall survival was 11.0 months (3–74 months). On univariate analysis, survival was not affected by optimal/suboptimal debulking, platinum/doxorubicin-containing chemotherapy, or homologous/heterologous stromal components. Stromal components (>25%) adversely affected survival ( P = 0.02), and there was a trend to worse survival with serous compared with nonserous epithelial components ( P = 0.07). Cox regression (multivariate analysis) showed that SP tumors ( P = 0.04), suboptimal debulking ( P = 0.01), age ( P = 0.01), and tumors with serous epithelial component ( P = 0.05) were adverse independent prognostic factors. Type of chemotherapy and homologous/heterologous components ( P = 0.24) did not affect overall survival. In conclusion, our study suggests that SP-OCS have a worse survival outcome than EP tumors. Tumors with serous epithelial components adversely affected the survival compared with nonserous components. Larger studies are required to confirm these effects and to identify the optimum chemotherapy regimen for OCS.